Effect of Using Fermented Carrot Leaves in Rations on Organic Matter Consumption, Crude Protein, and Crude Fiber in Thin-Tailed Sheep - Nurcahyo, Ichbal; Septian, Mohamad Haris; Rahayu, Tri Puji (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
Agricultural waste in the form of carrot leaves (Daucus carota L) has potential as a source of feed for thin-tailed sheep. Fermented processing of carrot leaves aims to increase feed efficiency, make it last longer and can be used within a certain time. This research aims to add information and references for readers regarding the effect of using fermented carrot leaves (Daucus carota L) in rations on the consumption of organic matter (BO), crude protein (PK), and crude fiber (SK) in thin-tailed sheep. This research was carried out for fifty-six days from December 2022 to January 2023 at Kandang Waris Mendho Farm and at the Integrated Laboratory of Tidar University. The design used was a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications, P1: 60% concentrate + 40% pakchong forage, P2: 60% concentrate + 10% fermented carrot leaves + 30% pakchong forage, P3: 60% concentrate % + fermented carrot leaves 20% + pakchong forage 20%, P4: concentrate 60% + fermented carrot leaves 30% + pakchong forage 10%, P5: concentrate 60% + fermented carrot leaves 40%. The research results showed that fermented carrot leaves had no effect on (P>0.05) BO consumption and PK consumption, but had a significant effect on (P<0.05) SK consumption. The highest SK consumption was in P1 with a consumption value of 102.44 ± 7.74 g. It can be concluded that fermented carrot leaves do not interfere with PK and SK consumption levels.